PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS DI KANTOR DINAS SOSIAL KABUPATEN BOLAANG MONGONDOW TIMUR - Mokoagow, Novianti; Tohopi, Rustam; Nani, Yakob Noho (Gorontalo State University, 2025)
ABSTRACT The purpose of this study was to determine how public services for people with disabilities are in the Social Service Office of East Bolaang Mongondow Regency, seen from the aspects of tangible (physical evidence), empathy, reliability, responsiveness, and assurance. This research method uses a descriptive approach with qualitative data analysis. Data collection techniques used are observation, interviews, documentation. Based on the results of research in the field, the implementation of the principles of public service at the Social Service Office of East Bolaang Mongondow Regency seen from tangible, empathy, reliability, responsiveness, and assurance has been running quite well. In its implementation, there are still several problems found, namely the lack of facilities in the form of shelters for people with disabilities and not fully meeting the standards of the needs of people with disabilities. In terms of empathy, officers show concern and a friendly attitude, but have not been accompanied by special training to understand the needs of people with disabilities as a whole. In terms of responsiveness, the service is quite fast, but the response to complaints or special requests is not optimal. Meanwhile, the reliability or reliability of service shows consistency in providing services, although sometimes constrained by limited human resources and supporting facilities. From the assurance aspect, the trust of people with disabilities in the competence and professional attitude of officers is quite high, although there is still a need for improvement in terms of delivering information and inclusive service procedures. Overall, although there is a commitment from the Social Service in providing inclusive services, there is still a need for improvement in various aspects so that public services are truly friendly and appropriate for people with disabilities. Keywords: Public Services, People with Disabilities, Social Service ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pelayanan publik bagi penyandang disabilitas Di Dinas Sosial Kabupaten Bolaang Mongondow Timur, dilihat dari aspek tangible (bukti fisik), emphaty (empati)., reliability (kehandalan), responsiveness (daya tanggap), dan assurence (asuransi). Metode penelitian ini menggunakan pendekatan deskriptif dengan analisis data kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi. Berdasarkan hasil penelitian dilapangan bahwa penerapan prinsip pelayanan publik di Kantor Dinas Sosial Kabupaten Bolaang Mongondow Timur dilihat dari tangible, empathy, reliability, responsiveness, dan assurance sudah berjalan cukup baik. Dalam pelaksanaannya masih terdapat beberapa masalah yang ditemukan yaitu kurangnya fasilitas berupa rumah singgah bagi penyandang disabilitas dan belum sepenuhnya memenuhi standar kebutuhan penyandang disabilitas. Pada aspek empati, petugas menunjukkan kepedulian dan sikap ramah, namun belum diiringi dengan pelatihan khusus untuk memahami kebutuhan penyandang disabilitas secara menyeluruh. Dari sisi responsivitas, pelayanan cukup cepat, tetapi tanggapan terhadap keluhan atau permintaan khusus belum maksimal. Sementara itu, reliabilitas atau keandalan pelayanan menunjukkan konsistensi dalam pemberian layanan, meskipun terkadang terkendala oleh keterbatasan sumber daya manusia dan fasilitas pendukung. Dari aspek assurance, kepercayaan penyandang disabilitas terhadap kompetensi dan sikap profesional petugas tergolong cukup tinggi, meskipun masih perlu peningkatan dalam hal penyampaian informasi dan prosedur layanan secara inklusif. Secara keseluruhan, meskipun terdapat komitmen dari pihak Dinas Sosial dalam memberikan pelayanan inklusif, masih dibutuhkan peningkatan pada berbagai aspek agar pelayanan publik benar-benar ramah dan layak bagi penyandang disabilitas. Kata Kunci : Pelayanan Publik, Penyandang Disabilitas, Dinas Sosial